Hyperemesis in Pregnancy Study: a pilot randomised controlled trial of midwife-led outpatient care. (May 2016) - McParlin, Catherine; Carrick-Sen, Debbie; Steen, Ian N.; Robson, Stephen C.
Abstract: Objective: To assess the feasibility of implementing a complex intervention involving rapid intravenous rehydration and ongoing midwifery support as compared to routine in-patient care for women suffering from severe nausea and vomiting in pregnancy, (NVP)/hyperemesis gravidarum (HG). Study design: 53 pregnant women attending the Maternity Assessment Unit (MAU), Newcastle upon Tyne NHS Foundation Trust, Newcastle, UK with moderate-severe NVP, (as determined by a Pregnancy Unique Quantification of Emesis and Vomiting [PUQE] score ≥nine), consented to participate in this pilot randomised controlled trial (RCT). Subsequently 27 were randomised to the intervention group, 26 to the control group. Women in the intervention group received rapid rehydration (three litres Hartman's solution over 6 h) and symptom relief on the MAU followed by ongoing midwifery telephone support. The control group were admitted to the antenatal ward for routine in-patient care. Quality of life (QoL) determined by SF36.V2 score and PUQE score were measured 7 days following randomisation. Completion rates, readmission rate, length of hospital stay and pregnancy outcomes data were collected. Results: Groups were comparable at baseline. Questionnaire two return rate was disappointing, only 18 women in the control group (69%) and 13 women in the intervention groups (44%). Nonetheless there were no differences between groups on Day 7 in terms of QoL, mean PUQE score, satisfaction with care, obstetric and neonatal outcomes or readmission rates. However, total combined admission time was higher in the control group (94 h versus 27 h, p = 0.001). Conclusions: This study suggests that day-case management plus ongoing midwifery support may be an effective alternative for treating women with severe NVP/HG. A larger trial is needed to determine if this intervention affects women's QoL.